ANALISIS KARAKTERISTIK MINYAK TERHADAP TEGANGAN TEMBUS TIGA JENIS MINYAK SEBAGAI ALTERNATIF MINYAK ISOLASI TRANSFORMATOR - Aggraini, Ika Novia; Situngkir, Hoklan Roianri Rifki Rinaldi; Rodiah, Yuli; Rinaldi, Reza Satria; Arfan, Muhmammad (Foristek, 2025)
This research seeks to assess the influence of viscosity and moisture content on the breakdown voltage of canola oil, corn oil, and sunflower seed oil, as well as to evaluate the quality and properties of these oils as potential alternative liquid insulations for transformers. Transformer liquid insulation specifications according to SPLN 50-1982 and IEC 60247:1991 standards include a breakdown voltage of 30 kV/2.5 mm, a maximum moisture content of 30 ppm or 0.003%, and a kinematic viscosity of 40 cSt at 20°C. During the assessment of moisture content and viscosity, two oil conditions are examined: fresh oil and old oil after the breakdown voltage test. The test data indicates that moisture content and viscosity influence breakdown voltage. Specifically, canola oil, with a moisture content of 0.17% and a viscosity of 28 cSt, exhibits a breakdown voltage of 20.5 kV/2.5 mm; corn oil, with a moisture content of 0.11% and a viscosity of 27 cSt, demonstrates a breakdown voltage of 25.3 kV/2.5 mm; sunflower seed oil, with a moisture content of 0.12% and a viscosity of 26 cSt, shows a breakdown voltage of 21.5 kV/2.5 mm. Nevertheless, the test findings indicate that the breakdown voltage fails to comply with the transformer insulating oil requirement.